(untitled) (Dhaka University Journal of Biological Sciences, 2016)
The storage mycoflora associated with seeds of 21 accessions of Corchorus capsularis L. were isolated and identified. Blotter, Paper towel and Agar plate methods were used to isolate the fungi associated with seeds. A total of ten species of fungi viz. Aspergillus flavus, A. fumigatus, A. niger, A. terreus, Curvularia lunata, Colletotrichum corchori, Fusarium oxysporum, Eurotium sp., Penicillium sp. and Rhizopus stolonifer were isolated from the selected jute seeds. Aspergillus spp. and Colletotrichum corchori were predominant in most of the jute accessions. Accession No. A-3047 showed the highest fungal incidence and Accession Nos. A-3361, A-2734 and A-877 showed the lowest. Accession No. A-3361 showed the highest seed germination while Accession No. A-3309 showed the lowest. Mortality of seedling showed the highest in Accession No. A-3309 and the lowest in Accession No. A-3361. Physical purity of seed recorded the highest in Accession No. A- 3361 and the lowest in Accession No. A-3309. There were negative correlation between percentage of fungi and percentage of germination and between percentage of fungi and physical purity of seeds. Positive correlation was observed between percentage of fungi and seedling mortality and between purity of seed and germination of seed. Dhaka Univ. J. Biol. Sci. 25(1): 9-17, 2016